Translating Neonatal Resuscitation Guidelines Into Practice in Brazil - de Almeida, Maria Fernanda B; Guinsburg, Ruth; Weiner, Gary M.; Penido, Marcia G.; Ferreira, Daniela M L M; Alves, José Mariano S; Embrizi, Laís F; Gimenes, Carolina B.; Mello E Silva, Nathalia M.; Ferrari, Lígia L; Venzon, Paulyne S.; Gomez, Dafne B.; et al. (American Academy of Pediatrics (AAP), 2022)
BACKGROUND AND OBJECTIVES: The Brazilian Neonatal Resuscitation Program releases guidelines based on local interpretation of international consensus on science and treatment recommendations. We aimed to analyze whether guidelines for preterm newborns were applied to practice in the 20 Brazilian Network on Neonatal Research centers of this middle-income country. METHODS: Prospectively collected data from 2014 to 2020 were analyzed for 8514 infants born at 230/7 to 316/7 weeks' gestation. The frequency of procedures was evaluated by gestational age (GA) category, including use of a thermal care bundle, positive pressure ventilation (PPV), PPV with a T-piece resuscitator, maximum fraction of inspired oxygen (Fio2) concentration during PPV, tracheal intubation, chest compressions and medications, and use of continuous positive airway pressure in the delivery room. Logistic regression, adjusted by center and year, was used to estimate the probability of receiving recommended treatment. RESULTS: For 3644 infants 23 to 27 weeks' GA and 4870 infants 28 to 31 weeks' GA, respectively, the probability of receiving care consistent with guidelines per year increased, including thermal care (odds ratio [OR], 1.52 [95% confidence interval (CI) 1.44-1.61] and 1.45 [1.38-1.52]) and PPV with a T-piece (OR, 1.45 [95% CI 1.37-1.55] and 1.41 [1.32-1.51]). The probability of receiving PPV with Fio2 1.00 decreased equally in both GA groups (OR, 0.89; 95% CI, 0.86-0.93). CONCLUSIONS: Between 2014 and 2020, the resuscitation guidelines for newborns <32 weeks' GA on thermal care, PPV with a T-piece resuscitator, and decreased use of Fio2 1.00 were translated into clinical practice.